OPTIMALISASI KESIAPAN SEKOCI DALAM KEADAAN DARURAT GUNA MENINGKATKAN KESELAMATAN CREW DI MV. TONASA LINES XV - Muhammad Al Dhafa Akbar; I Kadek Laju; Rizal Rochmansyah; Nelfi Erlinda; Rosnani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT Lifeboats are the only safety equipment that can save the crew in an emergency. This study aims to determine the maintenance process and crew skills in operating lifeboats. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. Observations were made to determine the lifeboat maintenance process, the condition of lifeboat parts, and crew skills in operating lifeboats. Meanwhile, interviews were conducted with the Captain, chief officer, third officer and third engineer to obtain in-depth information regarding the technical problems that occurred. The research findings revealed that maintenance on the lifeboats on the MV. Tonasa Lines XV was not carried out according to the planned maintenance schedule. Furthermore, the crew was deemed incompetent in operating the lifeboats, resulting in delays in launching them. This, in turn, left them unprepared for emergencies. Suggested solutions include improving lifeboat maintenance in accordance with SOLAS 1974 regulations and providing training to the crew on lifeboat operating procedures.